What is the Role of T.E.A Concept Between Positive Recommendation and Behavioural Intention to Purchase in Social Media? - Tun, Phyo Min (The South East Asian Journal of Management, 2022)
Research Aims: This study explores the antecedents of customers’ behavioural intention to purchase on the social media platform. In addition, the T.E.A concept, the group of consequences of positive recommendation (PR), is developed by amalgamating trust (T), easiness (E), and amusement (A). Design/Methodology/Approach: The data was collected from 260 random social media users from Myanmar. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed to examine the observed variables, and structural equation modelling (SEM) techniques were used to estimate the hypotheses in AMOS software. Research Findings: The results disclose that the T.E.A concept is fully mediating between positive recommendation and customers’ purchase intention. Theoretical Contribution/Originality: This study gives clear direction for future research studies, notably, in the online shopping context by providing the T.E.A concept. Managerial Implication in the South East Asian Context: The retailers on social media develop effective marketing strategies based on T.E.A concept to attract more customers, especially from South East Asian countries. Research Limitations & Implications: The vivid limitation of this study is focusing on only the positive recommendation as an antecedent of the T.E.A concept and the findings of this study implicate both theoretically and practically the future research studies about customers’ behaviour in the online shopping context.